2022
DOI: 10.3389/fpls.2022.1040037
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and application of GO nanoparticles to augment growth parameters and yield in mungbean (Vigna radiata L.)

Abstract: Plant growth promotion has long been a challenge for growers all over the world. In this work, we devised a green nanomaterial-assisted approach to boost plant growth. It has been reported that carbon nanomaterials are toxic to plants because they can inhibit the uptake of nutrients if employed in higher concentrations, however this study shows that graphene oxide (GO) can be used as a regulator tool to improve plant growth and stability. Graphene oxide in different concentrations was added to the soil of mung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The amounts of chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids were increased significantly upon priming with IAA (Figure a–c and Table S5), with the amount of chlorophyll a (0.429 mg/g FW) and chlorophyll b (0.104 mg/g FW). Chlorophyll a levels were also observed to be significantly increased in the rGO-treated samples (Figure a), which has been reported in previous studies in the case of GO . Although both the rGO-treated and IAArGO-treated samples recorded higher chlorophyll a, b and carotenoid contents, in comparison to the untreated sample (Table S5), there was no significant change observed in the chlorophyll content between the untreated, rGO-treated, and IAArGO-treated samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amounts of chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids were increased significantly upon priming with IAA (Figure a–c and Table S5), with the amount of chlorophyll a (0.429 mg/g FW) and chlorophyll b (0.104 mg/g FW). Chlorophyll a levels were also observed to be significantly increased in the rGO-treated samples (Figure a), which has been reported in previous studies in the case of GO . Although both the rGO-treated and IAArGO-treated samples recorded higher chlorophyll a, b and carotenoid contents, in comparison to the untreated sample (Table S5), there was no significant change observed in the chlorophyll content between the untreated, rGO-treated, and IAArGO-treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll a levels were also observed to be significantly increased in the rGO-treated samples (Figure 9a), which has been reported in previous studies in the case of GO. 49 Although both the rGO-treated and IAArGO-treated samples recorded higher chlorophyll a, b and carotenoid contents, in comparison to the untreated sample (Table S5), there was no significant change observed in the chlorophyll content between the untreated, rGO-treated, and IAArGOtreated samples. Total chlorophyll content of the IAA-and rGO-treated samples was observed to be higher than the untreated sample (Table S5).…”
Section: Effect Of Rgo As a Biostimulant On Maizementioning
confidence: 88%
“…RNA-seq data showed that DEGs were also involved in the glutamine synthetase, glutamate dehydrogenase 1, cyanate hydratase, protein fluG-like, NRT1/PTR family genes and NifU nitrogenase gene. Study showed that graphene oxide promoted the number of root nodules per plant of mungbean plant [18]. Actually, V. angularis plants can convert atmospheric dinitrogen to ammonium by biological nitrogen fixation [63].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zhao et al [17] found that the enriched functional groups on the surface of graphene could help plants absorb more macronutrients from the medium. Furthermore, a recent study showed that an appropriate amount of graphene oxide promoted the length of roots and shoots, the number of leaves, root nodules per plant, the number of pods, and the seeds per pod of mungbean plants [18]. Despite many researchers have conducted studies on the effects of graphene on plant growth, but few studies provided the molecular mechanisms that explored the graphene interaction with Leguminosae plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation